Systematic literature review of the obstacles in managing electronic records in mobile environment / Nurussobah Hussin ... [et al.] - Hussin, Nurussobah; Azmi, Ilylia Azuar; Mat Yatin, Saiful Farik; Wan Abdullah, Wan Abd Malek; Zulkipli, Fatin Nur (Faculty of Information Management, 2023)
As a rapidly advancing field within information and communication technology (ICT), mobile technology introduces new challenges to records management practices. The proliferation of mobile and wireless devices presents indirect challenges in effectively managing electronic records. To investigate the issues and challenges associated with managing electronic records in a mobile environment across various fields, this study relied on the selected databases of ScienceDirect, Emerald Insight, Scopus, and IEEE Xplore. By conducting a comprehensive review of previous literature published between 2015 and 2022 in the context of the mobile environment, this study presents its findings, encompassing aspects such as the background, research strategy, subject, and year of publication in the selected studies. Drawing from these findings, the identified issues and challenges are examined, and potential directions for future research are discussed. Overall, this study contributes to a deeper understanding of the utilization of electronic records in a mobile environment, highlighting key concerns and offering insights for further exploration.